Enhancing financial well-being and saving behavior: Do family, peers, and financial behavior matter? - Tina Sulistiyani; Desta Rizky Kusuma; Made Galih Wisnu Wardana (Universitas Ahmad Dahlan, 2026)
Purpose-This study examines how family financial socialization and peer influence affect saving behavior and financial well-being. It investigates financial behavior as a mediating variable among students in Yogyakarta, Indonesia. Young people are increasingly financially independent yet prone to consumerism, so understanding the roles of socialization and financial behavior in shaping saving habits and financial well-being is crucial. Methodology-A quantitative survey was conducted with 141 Generation Z students enrolled in universities in Yogyakarta, Indonesia, who manage their own income or allowance, selected using purposive sampling. Data were analyzed using partial least squares structural equation modeling with SmartPLS. Findings-Family financial socialization positively influences financial behavior, saving behavior, and financial well-being, while financial behavior positively influences saving behavior and financial well-being. Financial behavior mediates the effect of family financial socialization on saving behavior and financial well-being, confirming its role as the main pathway from family socialization to financial outcomes. In contrast, peer influence shows no meaningful effect on financial behavior, saving behavior, or financial well-being, and the mediating role of financial behavior in these relationships is also not supported. Research Limitations-The cross-sectional design cannot capture changes in financial behavior over time, and the sample is limited to Generation Z students in Yogyakarta, Indonesia, so caution is warranted when generalizing the findings to other populations. The use of self-report measures may also introduce perception and social desirability bias. Novelty-This study simultaneously tests family financial socialization, peer influence, financial behavior, saving behavior, and financial well-being within a single model and demonstrates that family socialization and personal financial behavior play a more dominant role than peer influence in explaining saving behavior and financial well-being. The results highlight the need for future research on other social factors (e.g., social media, digital financial literacy, financial self-efficacy) and for longitudinal and cross-context designs to deepen understanding of how financial well-being develops among younger generations.